Pharmaceuticals in wastewater from a small wastewater treatment plant in the context of the new Wastewater Directive - Włodarczyk-Makuła, Maria; Kamizela, Tomasz (Instal, 2024)
Work is currently underway in European Union member states to update the EU Wastewater Directive No. 91/271/EEC on urban wastewater treatment. The proposed changes, among other things, include monitoring the concentration of micropollutants relevant to human health, in treated wastewater discharged to surface waters. This includes micropollutants belonging to the group of pharmaceuticals and cosmetics, as well as microplastics. The study of pharmaceuticals proposes to limit the scope of analysis to the determination of 12 compounds, but other active compounds from this group of micropollutants are also identified in wastewater. The purpose of this study was to determine the concentration of pharmaceuticals in wastewater collected from an example small wastewater treatment plant. The qualitative analysis identified the presence of 89 compounds belonging to different groups of active compounds. Quantitative analysis of individual compounds showed varying concentrations: from below the limit of quantification to 2.0µg/L.